Arterial hypertension after myocardial infarction and ischemic stroke: prevalence and quality of control - Yahenskyi Андрій; Pavelko Михайло; Sichkaruk Ірина; Zubyk Ростислав (Psychosomatic Medicine and General Practice, 2019)
Introduction. Arterial hypertension is one of the major risk factors for myocardial infarction and stroke. Arterial blood pressure should be closely monitored in patients with recent myocardial infarction and ischemic stroke for many reasons, primarily to prevent further damage of target organs and complications. Goal. Compare the prevalence of hypertension and the factors that affect its control in patients in long term follow-up (more than 2 years) after ischemic stroke and myocardial infarction. Materials and methods. Informed consent to participate in the study was given by 265 patients with myocardial infarction and 166 patients with ischemic stroke. The time from hospitalization for the index event to inclusion in the study for patients with myocardial infarction was 2.3 ± 1.8 years, for patients with ischemic stroke - 2.6 ± 2.0 years. Anthropometric parameters, general clinical examination, blood pressure measurement, laboratory examination (lipids, glucose, creatinine) were collected for all subjects. In addition, a questionnaire was conducted assessing the drugs received by the patient, adherence to treatment, the patient’s knowledge of the main risk factors and the application of measures to control them. Results. The study revealed that patients after myocardial infarction and ischemic stroke did not differ significantly in age and had similar profile of risk factors, indicating the etiological affinity of these diseases. Arterial hypertension was found more frequently after ischemic stroke (77.7% vs. 69.1%, p = 0.045). In addition, patients with ischemic stroke had a poorer lipid profile and less physical activity. Unacceptably low levels of arterial hypertension control was detected in both groups. Achievement of target blood pressure was found in only 23.0% of patients after ischemic stroke and in 26.1% of patients after myocardial infarction (p = 0.52). However, the number of antihypertensive drugs was insufficient in both groups. A separate group of patients with excessively low blood pressure (SBP <110 mm Hg and / or DBP <70 mm Hg) was selected. Excessive blood pressure reduction was registered in 12.7% of patients after MI and 8.9% after IHI (p = 0.23), more often in women. In addition, patients in the group with excessively low blood pressure were more likely to be older, had a lower body mass index and heart rate